Developing a Boiling Test to Quantify Effective Bonding of Aggregates with Binder - Cuciniello, Giacomo (My University, 2013)
The main purpose of asphalt mixture production is the coating of mineral aggregates with asphalt binder within a reasonable time frame. Coating is required as it affects mixtures workability (e.g., lubricant effect of binder film), as well as durability (e.g., preventing mixtures from moisture damage). However, mixing time needs to be controlled since it greatly influences both plant productivity (i.e., amount of mixture produced per hour) and binder aging, which is caused by the loss in volatiles due to temperature and air flow during mixing. In light of this, mixing temperature is selected to properly reduce binder?s viscosity below a limit to ensure proper coating in a time frame of 90 seconds. Current viscosity limits used for selecting mixing and compaction temperatures are valid only for unmodified binders, which generally exhibit a linear Newtonian behavior; furthermore, the literature indicates that these limits were introduced solely based on practical considerations without a fundamental understanding of the physical and chemical processes driving the production of this material. A guideline for the selection of compaction temperatures for modified binders, which are nowadays very popular, is not available to practitioners. Mixing temperatures calculated based on current recommendations for viscosity limits are often higher than 150C and they become even more excessive when modified binders are used. The usage of these temperatures raises concerns in terms of energy cost, sustainability and safety. Thus, transportation agencies and practitioners are currently challenged with the need of reducing the mixing temperatures during production without negatively affecting the level of coating or performance of mixtures. This can only be accomplished by providing a clear understanding of the main factors and variables that affect coating, and by showing the influence of coating on the susceptibility of asphalt mixtures to moisture damage. Reducing mixing temperatures will result in increasing viscosity. The effect of increased viscosity on both coating and the adhesive bond between the binder and aggregates has not been properly investigated in the past. In this thesis, effects of coating are considered based on two different points of view: (a) extent of coating, which is defined as the amount of dry aggregates coated by binder after mixing for a given time before compaction; and (b) the quality of coating which is defined as a qualitative description of the adhesive bond between binder and aggregate. Initially a procedure based on aggregates water absorption (ASTM C127 ? 07) was developed for determining the extent of coating. Results from this procedure showed that the extent of coating is affected by low shear viscosity and asphalt content, but highlighted that the extent of coating is not sufficient for assessing moisture susceptibility of mixtures. It was determined that moisture damage of mixtures is more dependent on the binder-aggregate bond strength rather than the extent of coating. For this reason, a modified boiling test procedure based on the ASTM D3625 ? 1996 was introduced and developed for evaluating the quality of coating. Results from the modified boiling test have shown that the quality of coating is highly affected by low shear viscosity, binder modification, and aggregate type. Furthermore, a time-dependency effect of the quality of coating was observed for certain combinations of asphalt binders and aggregates. The analysis of the boiling test results , which is based on visual inspection of aggregates surface post boiling, was validated using the acid ? base titration procedure recommended in the UNI EN 12697-11 2012 (E). In addition, the Bitumen Bond Strength (BBS) test (AASHTO TP 91-12), was included in the experimental study to evaluate if the application/production temperature affects the moisture susceptibility of the inderaggregates systems. Results showed that the modified boiling test and the BBS test are correlated. Furthermore, the boiling procedure was validated using the Indirect Tensile Strength (ITS) test, (AASHTO T 283). A preliminary correlation between the boiling test and the ITS showed that the proposed procedure is promising for the evaluation of the quality of coating and can be used as a surrogate for estimating the susceptibility of asphalt mixtures to moisture damage. The ITS results in combination with the analysis from the boiling test were used to provide preliminary design limits. Results from this thesis show that quantifying the extent of coating is not sufficient for predicting moisture susceptibility. Indeed, the quality of coating needs to be considered when assessing moisture damage of mixtures. Findings from the modified boiling test have pointed out that the quality of coating is affected not only by viscosity, but also by binder modification and aggregate type. In summary, the developed modified boiling test can be used as a simple procedure for selecting mixing temperature that will ensure sufficient extent and quality of coating, both of which have significant effect on asphalt-aggregate mixture moisture susceptibility.